Customer prioritization - Gracner, Maria (Economic and business review, 2025)
This study examines customer prioritization, a strategic practice where businesses allocate resources and efforts based on customer value. While its significance in international marketing continues to grow, limited research exists on how customer prioritization is understood and applied in international firms operating across diverse cultural contexts. Addressing this gap, the study explores how international-marketing managers conceptualize customer prioritization and identifies its key components. Using a qualitative methodology, the study conducted in-depth interviews with Slovene international-marketing and sales managers from 13 export-oriented firms. Thematic analysis, guided by the Gioia methodology, identified four central themes: prioritization tactics and strategies, international customer profitability, headquarters–subsidiary relationships, and customer relationship management. The results indicate that companies adopt varied prioritization strategies influenced by factors such as product lines, customer size, industry significance, and the importance of foreign markets. Furthermore, subsidiaries play a pivotal role in collecting and relaying local market knowledge to headquarters, facilitating effective customer prioritization. This research advances the conceptual understanding of customer prioritization as a dynamic capability that shapes customer relationship management strategies in international firms and can enhance profitability in foreign markets.
Keywords: mednarodno trženje; strategija trženja; vedenje potrošnikov